Efektivitas Media Neo Snake and Ladder Game Terhadap Kemampuan Komunikasi Matematis Siswa - Fauzi Fadliansyah (EduBasic Journal: Jurnal Pendidikan Dasar, 2019)
The purpose of this study was to determine the effectiveness of Neo Snake and Ladder Game media in increasing students' mathematical communication skills. The population in this study were fourth grade students of Sukaratu 4 Elementary School, Majasari District, Pandeglang Regency in the Academic Year of 2019/2020. The reseracher used simple random sampling. The data collection used tests of mathematical communication skills, observation, and documentation. The results showed that (1) the classical completeness test of students' mathematical communication skills reached a minimum limit of 68, (2) mathematical communication skills of Neo Snake and Ladder Game media had reached classical completeness of 75% and (3) the increase in average of mathematical communication skills using media Neo Snake and Ladder Games were better than the average mathematical communication skills of students without using Neo Snake and Ladder Games media. Based on the above results, it can be concluded that Neo Snake and Ladder Games media are effective in improving students' mathematical communication skills.